2017
DOI: 10.1177/1077546317726637
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic characteristics of horizontally curved bridges

Abstract: Horizontally curved bridges have complicated dynamic characteristics because of their irregular geometry and nonuniform mass and stiffness distributions. This paper aims to develop a simplified and practical method for the calculation of the natural frequencies and mode shapes of horizontally curved bridges that would be of interest to bridge engineers for the estimation of the seismic response of these types of bridges. For this purpose, a simple three-degree-of-freedom (3DOF) dynamic model for free vibration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…To model the abutments, non-linear zero Length elements were used (Table 4) and the shear wave velocity was obtained from PEER (Table 5). The accuracy of the bridge finite element model was verified by the results of Tondini and Stojadinovic [28] and Amjadian and Agrawal [29]. The results of the current study by the mentioned papers are compared and shown in Table 6.…”
Section: Numerical Studymentioning
confidence: 68%
“…To model the abutments, non-linear zero Length elements were used (Table 4) and the shear wave velocity was obtained from PEER (Table 5). The accuracy of the bridge finite element model was verified by the results of Tondini and Stojadinovic [28] and Amjadian and Agrawal [29]. The results of the current study by the mentioned papers are compared and shown in Table 6.…”
Section: Numerical Studymentioning
confidence: 68%
“…This can be done by adjusting the positions of the columns shown in Figure a. More details on this can be found in the previous publications of the authors . The subtended angle of the deck β is the key geometrical parameter of the bridge prototype.…”
Section: Resultsmentioning
confidence: 99%
“…More details on this can be found in the previous publications of the authors. 17,39 The subtended angle of the deck β is the key geometrical parameter of the bridge prototype. This parameter is proportional to the curvature of the deck κ through β = κL = L/R O , where L is the length of the deck.…”
Section: Influence Of the Curvature Of The Deck (κ = β/L)mentioning
confidence: 99%
“…However, the use of such equivalent bridges is limited to curved bridges with certain limits on their subtended angle and regularity. Irregular geometry and nonuniform mass distribution in curved bridges lead to an excessive in-plane rotation of the superstructure compared to an equivalent straight bridge [19]. Unseating of the superstructure is one of the primary collapse modes of horizontally curved bridges, exacerbated by the increased inplane rotation of the superstructure [20].…”
Section: Introductionmentioning
confidence: 99%